2010
DOI: 10.3201/eid1605.091894
|View full text |Cite
|
Sign up to set email alerts
|

Contagious Period for Pandemic (H1N1) 2009

Abstract: Most infected persons shed live virus after fever abated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 15 publications
6
41
1
Order By: Relevance
“…However, the sensitivity of the virus to oseltamivir in the 2009-2010 season as evaluated by IC 50 was quite comparable to that of seasonal H1N1 without H275Y mutation [10]. A long virus shedding period has also been reported, by RT-PCR, for young H1N1pdm patients [21][22][23]. The reason for the long virus persistence, irrespective of low IC 50 of oseltamivir to H1N1pdm, is not clear.…”
Section: H275y Mutation After Therapy and Ic 50mentioning
confidence: 76%
“…However, the sensitivity of the virus to oseltamivir in the 2009-2010 season as evaluated by IC 50 was quite comparable to that of seasonal H1N1 without H275Y mutation [10]. A long virus shedding period has also been reported, by RT-PCR, for young H1N1pdm patients [21][22][23]. The reason for the long virus persistence, irrespective of low IC 50 of oseltamivir to H1N1pdm, is not clear.…”
Section: H275y Mutation After Therapy and Ic 50mentioning
confidence: 76%
“…13 Finally, in a Canadian study, 43 community patients with pandemic H1N1 had a nasopharyngeal specimen collected on day 8 of their illness: 74% were PCR-positive and 19% were culture-positive. 33 One subject from our study who demonstrated the shedding of live virus up to day 8 will be considered further. She was a 34-year-old woman, of South-Asian origin, who had no comorbidities, and did not take regular medicine.…”
Section: Discussionmentioning
confidence: 98%
“…These data are consistent with other recent studies that suggest that pandemic H1N1 may be contagious for a longer period of time than seasonal flu. 13,33 This has clear implications for pandemic infection control and self-isolation guidelines. However, despite finding that live virus shedding continued for over 4 days in most subjects, fomites contaminated with virus were found in only two instances, involving only one subject.…”
Section: Discussionmentioning
confidence: 99%
“…Current plans should be reviewed and revised based on lessons learned during the pH1N1 pandemic. 6,7,[17][18][19][20][21][22] However, as that experience illustrated, we can never conceive of all possible scenarios ahead of time, will always want additional information, and need a flexible framework for making and communicating decisions. Despite advances in vaccine production and distribution, it is unlikely that a well-matched vaccine will be available at the onset of the next pandemic.…”
Section: Discussionmentioning
confidence: 99%